Characterization of a bicistronic retroviral vector composed of the swine vesicular disease virus internal ribosome entry site. - Chen, B F (1993)
We cloned the 5' nontranslated region (NTR) from the genome of swine vesicular disease virus (SVDV), a member of the family Picornaviridae, and used it to construct a bicistronic retroviral vector. The vector is characterized by coexpression of two genes from a single transcript. We found that inclusion of the 5' NTR of SVDV did not negate the viral vector titer. Protein analysis indicated that the 5' NTR could efficiently direct internal initiation, thus allowing the downstream gene to be translated. Translation of the internally initiated porcine growth hormone gene was about 30-fold less than that when the porcine growth hormone gene was at the upstream position in NIH 3T3 cells but was about equivalent to that in HeLa cells, implying that some cellular factors that stimulated internal initiation of the SVDV 5' NTR are present in HeLa cells. However, in G418-selected clones, the Neor-encoding gene was expressed with equivalent efficiency either at a downstream position or at an upstream position in either NIH 3T3 or HeLa cells. Compared with the conventional double-gene vector or the U3-based vector, the bicistronic vector coexpressed two genes much more efficiently, owing to elimination of promoter interference. Furthermore, this type of vector infected and expressed the target genes efficiently in two primary cell lines, rat embryo and human skin fibroblast cells, which we tested. These experimental data suggest a better design for the retroviral vector and provide evidence that internal initiation of the SVDV 5' NTR was stimulated cell specifically.